Pain management in veterinary practice - Egger, Christine M.; Love, Lydia; Doherty, T. J. (Tom J.) (Ames, Iowa Wiley Blackwell, 2014)
Pain Management in Veterinary Practice provides veterinary practitioners with the information needed to recognize and manage pain in a wide range of large, small, and exotic animal species. Encompassing acute, adaptive, and chronic, maladaptive pain, the book provides an up-to-date review of the physiology and pathophysiology of pain. Pain Management in Veterinary Practice offers specific strategies for addressing pain in animals, including local and regional analgesia, continuous rate infusions, and novel methods of analgesic drug delivery. With comprehensive information on the pharmacokinetic and pharmacodynamic characteristics of analgesic drugs, the book goes beyond pharmaceutical options to incorporate scientific information on techniques for complementary treatment, including physical therapy, acupuncture, chiropractic techniques, and nutritional strategies. Pain Management in Veterinary Practice is a valuable resource for developing pain management protocols in the veterinary clinic. --
Introduction: pain: an Issue of animal welfare / Alice Crook -- Anatomy, physiology, and pathophysiology of pain / Yael Shilo and Peter J. Pascoe -- Mechanisms of cancer pain / Cholawat Pascharinsak and Alvin J. Beitz -- Opioids / Tanya Duke-Novakovski -- Nonsteroidal anti-inflammatory drugs and corticosteroids / Stuart Clark-Price -- Local anesthetics / Kip A. Lemke -- Adrenoceptor agonists / Reza Seddighi -- Nontraditional analgesic agents / Lydia Love and Dave Thompson -- Novel methods of analgesic drug delivery / Lesley J. Smith -- Pharmacokinetic principles for the design of intravenous infusions / Bruno H. Pypendop -- Canine rehabilitation / Lowri Davies -- Equine rehabilitation / Lowri Davies -- Custom external coaptation as a pain management tool: veterinary orthotics and prosthetics / Martin W. Kaufmann and Patrice M. Mich -- Myofascial pain symdrome in dogs / Rick Wall -- Traditional Chinese herbal medicine and homeopathy in pain management / Lynelle Graham, Mona Boudreaux, and Steve Marsden -- Mechanisms of acupuncture analgesia / Shauna Cantwell -- Equine acupuncture / Arthur I. Ortenburger -- Canine chiropractic and pain management / Robin Downing -- Equine chiropractic / Henry S. Adair -- Recognition and assessment of acute pain in the dog / Kate L> White -- Treatment of acute pain in the dog / Kate L. White -- Recognition and assessment of chronic pain in dogs / Anna Hielm-Björkman -- Treatment of chronic pain in dogs / Anna Hielm-Björkman -- The recognition and assessment of pain in cats / Kersti Seksel -- Treatment of acute pain in cats / Jacob A. Johnson -- Treatment and assessment of chronic pain in cats / Bonnie Wright and Jessica K. Rychel -- Cancer-associated pain and its management / Lydia Love and Lisa DiBernardi -- Recognition and treatment of pain in the small animal critical care patient / Jane Quandt -- Recognition and assessment of pain in horses / Emma Love -- Treatment of acute and chronic pain in horses / Bernd Driessen and Laura Zarucco -- Recognition and assessment of pain in ruminants / Kevin J. Stafford -- Treatment of acute and chronic pain in ruminants / Alexander Valverde -- Recognition and treatment of pain in cmelids / Tamara Grubb -- Recognition and treatment of pain in pet pigs / Kristie Mozzachio and Valarie V. Tynes -- Recognition and assessment of pain in small exotic mammals / Lesa Thompson -- Treatment of pain in small exotic mammals / Cheryl B. Greenacre -- Recognition and treatment of pain in birds / Karen L. Machin -- Recognition and treatment of pain in reptiles, amphibians, and fish / Lysa Pam Posner and Sathya K. Chinnadurai -- Integrating pain management into veterinary practice / Robin Downing -- Pain management in hospice and palliative care / Keri Jones -- Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Pain in animals -- Treatment